Processes of linguistic accommodation within the Puerto Rican diaspora in New Jersey - Yhosep Barba Blanco (Revista Nebrija de Linguistica Aplicada a la Enseñanza de Lenguas)
This article explores the sociocultural and linguistic experiences of eight Puerto Ricans who have migrated to the state of New Jersey. While previous research has shown how the Puerto Rican diaspora has linguistically accommodated across the United States, this study investigates the role of linguistic attitudes and accommodation processes in the maintenance, reinforcement, or erasure of sociophonological and lexical features in Puerto Ricans who have migrated to New Jersey. Through a Grounded Theory approach, this study discloses how these individuals navigate linguistic norms, maintain cultural identity, and challenge racial and linguistic discrimination. Findings show a range of linguistic accommodation strategies, varying from preserving their Puerto Rican Spanish phonological features to code-switch (Spanish-English) and terminology explanation to have mutual understanding when talking to other Spanish-speaking communities.